Pengaruh Motivasi dan Minat pada Prestasi Belajar Peserta Didik di Sekolah Dasar 071059 Hilibadalu pada Mata Pelajaran IPS - Tien, Elvis; Halawa, Ellen Margaretha; Telaumbanua, Indah Anjelita; Gulo, Family Kristiani; Zebua, Eza; Halawa, Ritasman; Harefa, Rukun Iman; Harefa, Edward (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to prove the accuracy of the hypothesis regarding the influence of students' motivation and interest in learning-on-learning achievement in elementary school 071059 Hilibadalu. The research method used is a quantitative approach. Data was collected through questionnaires. Data analysis uses a correlation test (pearson correlation coefficient) which examines the relationship between two or more variabels and a t-test, with the research subjects consisting of 57 students in grade V of SD Negeri 071059 Hilibadalu. Based on the results of data analysis, it is known that there is an influence of motivation, interest in social studies learning achievement of elementary school 071059 Hilibadalu, this is evidenced by the results of sig. 0.004 < 0.05 and the results of X2 sig. 0.000 < 0.05, the results of the T test on X1 2.981 > 2.00247 and the results on the T test X2 6.025 > 2.00247, from these results it can be concluded that H0 was rejected and H1 was accepted. The results of this study can provide new insights for educators and policy organizers regarding the importance of increasing students' interest and motivation in social studies learning in the future